1993
DOI: 10.1107/s010876739201242x
|View full text |Cite
|
Sign up to set email alerts
|

X-ray dynamical diffraction in Ge with a zero-real-part scattering factor

Abstract: X-ray dynamical diffraction induced only by the imaginary part of the scattering factor was measured using a Ge perfect crystal. The 844 integrated reflecting intensities near the K-absorption edge were measured in both the Bragg and the Laue cases. The intensities show the characteristic variations for the scattering factor having no real part, which agree well with theoretical predictions. There remains a slight difference between the theoretical [Fukamachi & Kawamura (1993). Acta Cryst. A49, 384-388] and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1995
1995
1999
1999

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The case where q = 1 (χ hr = 0). In this case, the diffraction is induced only by the imaginary part of the atomic scattering factor [8,10,12,14,15] and the dispersion surface in the symmetrical Laue case is similar to that in the symmetrical Bragg case with no absorption [14]. According to (35), L = X Because of the anomalous absorption and penetration, the direction of the Poynting vector of the total fields in the crystal does not change with the distance from the crystal surface; it only changes when the two fields flow in the same direction.…”
Section: 23mentioning
confidence: 99%
See 1 more Smart Citation
“…The case where q = 1 (χ hr = 0). In this case, the diffraction is induced only by the imaginary part of the atomic scattering factor [8,10,12,14,15] and the dispersion surface in the symmetrical Laue case is similar to that in the symmetrical Bragg case with no absorption [14]. According to (35), L = X Because of the anomalous absorption and penetration, the direction of the Poynting vector of the total fields in the crystal does not change with the distance from the crystal surface; it only changes when the two fields flow in the same direction.…”
Section: 23mentioning
confidence: 99%
“…With x-rays from a tunable synchrotron radiation source, it is possible to select the ratio of F hr and F hi , and make |F hr | |F hi |, or even F hr = 0, near the absorption edge of a component atom in the crystal [4][5][6][7][8][9][10][11][12][13][14][15]. In 1995, Fukamachi et al found that the shape of the dispersion surface is strongly related to the ratio of F hr and F hi [13].…”
Section: Introductionmentioning
confidence: 99%
“…As q increases, with the results that the contribution of the imaginary part becomes more and more comparable to that of the real part, the diffraction gradually decreases. When the diffraction is induced only by the imaginary part [3][4][5][6][7], the deviation is the least.…”
mentioning
confidence: 99%